Lieutenant versus Marshal. Double Challenge to Post-Vaubanian Tradition in the Texts of Scottish Military Engineer Charles Bisset, 1751–1778 (Theatrum historiae, 2019)
This text represents a study in cultural history of war and warfare and adheres more specifically to the genre of historical anthropology. It deals with a problem of concept of so called crisis of permanent fortification, commencing in the period after the Treaty of Aix-la-Chapelle which terminated the War of the Austrian Succession. One of the very few critics of this new concept, which favoured field operations and decisive battles over established methods of siege warfare, was Scottish military engineer Charles Bisset, an author of highly advanced book on theory of fortification, published in 1751, which offered a way out of the perceived crisis. Despite being protected by the supreme commander of British armed forces, William, Duke of Cumberland, Bisset’s propositions were unexpectedly and unceremoniously rejected and he was discharged from the corps of military engineers. In the absence of almost any documentary sources, this text attempts to offer an anthropologic analysis of such abrupt and most unusual ending of Bisset’s career, linking it with lasting and deep cultural trauma associated with the subterranean and pyrotechnical dimension of siege warfare, which represented a major focus of Bisset’s work.
Keywords: fortifications; Great Britain; military engineering; 18th century; Charles Bisset